2013
DOI: 10.1136/heartjnl-2013-304613.488
|View full text |Cite
|
Sign up to set email alerts
|

GW24-e0061 Microvascular dysfunction in remote myocardium predict left ventricular remodelling in acute infarction

Abstract: Objectives Coronary flow reserve in the non-infarcted myocardium has been reported to be impaired after the onset of myocardial infarction, however, the clinical significance of microvascular dysfunction in the non-infarcted myocardium has not fully examined. This study was designed to assess the relationship between coronary flow reserve in the remote region and left ventricular remodelling in the 6-month follow-up after acute myocardial infarction. Methods We studied 36 patients (mean age 58.8), with singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…MCE can be used for both qualitative and quantitative analysis. In previous studies, coronary flow reserve (CFR), which is one of the MCE quantitative parameters, was shown to correlate with MV and adverse ventricular remodeling after AMI [ 28 , 39 , 40 ]. A recent study [ 41 ] also demonstrated that CFR is an independent predictor of MACE in patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…MCE can be used for both qualitative and quantitative analysis. In previous studies, coronary flow reserve (CFR), which is one of the MCE quantitative parameters, was shown to correlate with MV and adverse ventricular remodeling after AMI [ 28 , 39 , 40 ]. A recent study [ 41 ] also demonstrated that CFR is an independent predictor of MACE in patients with AMI.…”
Section: Discussionmentioning
confidence: 99%